Computational study of water adsorption on the TiNi (110) surface - Chauke Vukosi; Tshwane David; Ngoepe Phuti; Chauke Hasani (MATEC Web of Conferences)
TiNi (Nitinol) alloys exhibit unique properties such as low density, high strength, superelasticity and shape memory effector various applications in medical devices, and aerospace industry. Understanding their surface water interactions is crucial. This work employs the density functional theory to examine water adsorption on the TiNi (110) surface. The results indicated an exothermic adsorption process favouring the bridge site energetically. Electronic structure analysis revealed the dominance of d- orbitals and the presence of states at the Fermi level. The charge density difference suggested covalent bonding between water and the TiNi surface. Insights into TiNi's surface chemistry and reactivity, which are essential for the reduction of corrosion in aqueous environments, were investigated.